Alteration of 11β-Hydroxysteroid Dehydrogenase Type 1 and Glucocorticoid Receptor by Ethanol in Rat Liver and Mouse Hepatoma Cells - Zhaojie Meng; Xueying Bao; Ming Zhang; Shengnan Wei; Wenguang Chang; Jing Li; Li Chen; B. L. Grégoire Nyomba (Journal of Diabetes Research)
Alcohol is a potential risk factor of type 2 diabetes, but its underlying mechanism is unclear. To explore this issue, Wistar rats and mouse hepatoma cells (Hepa 1–6) were exposed to ethanol, 8 g·kg−1·d−1 for 3 months and 100 mM for 48 h, respectively. Glucose and insulin tolerance tests in vivo were performed, and protein levels of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) and glucocorticoid receptor (GR) in liver and Hepa 1–6 cells were measured. Alterations of key enzymes of gluconeogenesis phosphoenolpyruvate carboxykinase (PEPCK) and glucose 6 phosphatase (G6Pase), as well as glycogen synthase kinase 3a (GSK3α), were also examined. The results revealed that glucose levels were increased, and insulin sensitivity was impaired accompanied with liver injury in rats exposed to ethanol compared with controls. The 11β-HSD1, GR, PEPCK, G6Pase, and GSK3α proteins were increased in the liver of rats treated with ethanol compared with controls. Ethanol-exposed Hepa 1–6 cells also showed higher expression of 11β-HSD1, GR, PEPCK, G6Pase, and GSK3α proteins than control cells. After treatment of Hepa 1–6 cells exposed to ethanol with the GR inhibitor RU486, the expression of 11β-HSD1 and GR was significantly decreased. At the same time the increases in PEPCK, G6Pase, and GSK3α levels induced by ethanol in Hepa 1–6 cells were also attenuated by RU486. The results indicate that ethanol causes glucose intolerance by increasing hepatic expression of 11β-HSD1 and GR, which leads to increased expression of gluconeogenic and glycogenolytic enzymes.